OVERLAP SYNDROME IN A REFRACTORY CASE - Guchev, Filip; Mishevska Perchinkova, Snezana; Bozhinovski, Georgi; Damjanovska, Ljubinka (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
This is a report of the case of a 23 years-old girl with refractory dermatomyositis, complications in her treatment and the unfortunate fatal end. Dermatomyositis can be a notoriously difficult disease to treat, and remission is often elusive or short-lived despite aggressive therapy. In the years after the diagnosis, many aggressive modalities of treatment were tried, including rituximab. The patient had frequent exacerbations of the myositis, needed aggressive therapy and developed many side effects associated with the treatment. Most common of these were infections. After suffering severe stress, she developed fever, was diagnosed with sepsis and despite exhaustive treatment at the intensive care unit she passed away. Key words: dermatomyositis, refractory, immunosuppression, sepsis.     https://doi.org/10.55302/JMS2251093g